Potensi senyawa polifenol dalam ekstrak daun kelapa sawit untuk produk gel sunscreen alami - Sujaka, Romi; Siregar, Bimas Satrio; Saputri, Lestari Hetalesi (Jurnal Rekayasa Proses, 2025)
The bad effects of exposure to sunlights through the content of UltraViolet A (UVA) and UltraViolet B (UVB) in the long term can cause skin damage. One way of protection is through the using of sunscreen. This study aims to make a gel sunscreen from natural ingredients, polyphenolic compounds from oil palm leaf extract. The use of natural sunscreens has the advantage of the safety level of use when compared to synthetic sunscreens. The process of making sunscreen consists of several stages, namely raw material preparation (separating the leaves from the palm fornds, chopping, washing, and drying the palm leaves), extraction palm leaf by the maceration method (soaking and stirring powdered plam leaf with ethanol 96%) and making gel preparations by mixing palm leaf extract with methylparaben and a gel base, namely Hydroxy Propyl Methyl Cellulose (HPMC) and Carbopol. After the gel is made, the preparation is tested to obtain a sunscreen formulation that complies with SNI No 16-4399-1996. From the test results, several standard formulations were obtained, namely pH, spreadability, emulsion stability, antioxidant, viscosity, and SPF parameters. The best sunscreen gel product is the F2 (comparison of HPMC and Carbopol 70% : 30%) with a concentration of 1% palm leaf extract.